Paper Reviews of Agile Methodology Software Development - bin Mohamad Khairi, Aiman Mudzafar; bin Kamaruddin, Mohamad Zainal; Setyawan Widyarto (Proceedings of the Informatics Conference, 2020)
Abstract –There are many suggestions recently on how toimprove the software development process. While manydevelopers continue to control the development processusing the traditional methodologies, this AgileMethodology comes around. This new methodology takesthe development process to a higher level that creates anew challenge to any specific requirements. A sprightlymovement in this new methodology created newpractices such as Extreme Programming (XP), SCRUM,Lean Software Development (LSD), Crystal, Kanban andmany more. The study of this paper is to identify themajor changes and the implications to the industry.Firtsly, the authors will describe the meaning of AgileMethodology, followed by their characteristic,development process and the differences between AgileMethodology and traditional method. Secondly, theauthors will explain the differences of the practice inAgile Methodology. Last but not least, the authors willbring the readers to the conclusion of their idea of AgileMethodology which make this methodology produce amajor changes in project lifecycle